Influence of Measured Wheel Tread on Dynamics - Zhaotuan GUO; Maoru CHI; Tengyang XU (机车电传动)
By using computational multi-body dynamics simulation software SIMPACK, a dynamics simulation model of high-speed EMUs running in China was built. The actual measurement wheel tread which had serviced 50 000 km, 100 000 km, 150 000 km and 200 000 km effect on dynamic was analyzed. The analysis results showed that the critical velocity of the vehicle system increased with the increase of the service range, and then decreased with the increase of the service range, then increased with the increase of the service range and leveling off finally. With the increase of the wheel tread service mileage vertical stability index had not changed steadily, and the horizontal stability had been increased with the increase of the service mileage besides serving 100 000 kilometers. Derailment coefficient, lateral wheelset force and abrasion power larger changed with the increase of the wheel tread service range, and the weight loss rate changed a little with the increase of the wheel tread service range.